2017
DOI: 10.1111/jfpe.12591
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of operational parameters of jet cutting method on the size of Ca‐alginate beads

Abstract: A rarely used option for reduction the size of Ca‐alginate beads is the jet cutter, a rotating disk coupled to the output of the nozzle, and responsible for cutting the jet in smaller sizes. There are few systematic studies in the literature about this apparatus and its operational effects on the bead size. Therefore, this work aimed to investigate some operational parameters on the size of Ca‐alginate beads produced by dripping and jet cutting methods. First, physicochemical properties of different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…After falling down to this solution, alginate droplets formed insoluble particles with encapsulated thyme extract due to ion exchange (sodium ions from sodium alginate with calcium ions from crosslinking solution). When the process of particle formation was completed, the voltage generator was turned off and particles were left to harden for 2 hr (Paulo, Ramos, & Prata, ).…”
Section: Methodsmentioning
confidence: 99%
“…After falling down to this solution, alginate droplets formed insoluble particles with encapsulated thyme extract due to ion exchange (sodium ions from sodium alginate with calcium ions from crosslinking solution). When the process of particle formation was completed, the voltage generator was turned off and particles were left to harden for 2 hr (Paulo, Ramos, & Prata, ).…”
Section: Methodsmentioning
confidence: 99%
“…A maximum flow rate of 49 mL/ minute yielded beads of about 2 mm size. Increasing the rotational speed of the cutter decreased the bead size by 50% though increased the tangential velocity of the droplets leading to a larger space requirement for product collection [62]. Other parameters such as gravitational force, surface tension, viscosity and flow rate were also noted.…”
Section: Techniques Based On Drop Generation Methodsmentioning
confidence: 95%
“…The drops generated are generally in the size range of 120 μm to 3 mm. Paulo and colleagues [62] recently x-rayed the process parameters requisite for the generation of optimally suited calcium alginate beads using the jet cutter. A maximum flow rate of 49 mL/ minute yielded beads of about 2 mm size.…”
Section: Techniques Based On Drop Generation Methodsmentioning
confidence: 99%
“…The use of Equation 14for the prediction of optimum nozzle height is not convenient because the information of Oh number or droplet diameter is unknown. Paulo et al (2017) found that the current models for prediction of bead size could not be used in dripping process. For the case of liquid jet breaking up, the Equation (19) has been proposed for prediction of droplets size…”
Section: Proposed Methods For Prediction Of Nozzle Heightmentioning
confidence: 96%
“…In the dripping process, Paulo et al (2017) described the trials and errors to get spherical beads applicable for 2% alginate solution with liquid flow rate 49 mL/min (using nozzle size 1 mm which is equivalent to liquid jet velocity 1.04 m/s and formed a liquid jet before dripping) at nozzle height of 16-30 cm. The bead size was approximately 2.4 mm which is equivalent to about 2.8 mm of droplet sizes by using average shrinkage value 0.845 (Chan et al, 2009).…”
Section: Correlation Between Nozzle Height and Oh Numbermentioning
confidence: 99%